The housing security consequences of underemployment - Campbell, I.; Parkinson, S.; Wood, Gavin (2013)
This Positioning Paper introduces a research project that aims to provide an Australiawide analysis of the consequences of underemployment for housing security. It thereby explores the connection between an increasingly important but problematic feature of contemporary labour markets (underemployment) and a crucial dimension of housing research and policy (housing security). The empirical findings of the research will be presented in a Final Report. This Positioning Paper focuses on presenting the background research for the project, including conceptual issues, a review of the academic and policy literature, and an initial formulation of the methodology. The paper starts with the rationale for the project, from both an academic and a policy point of view. It then goes on to examine the current state of knowledge on underemployment as a feature of labour markets in Australia. The paper also reviews the literature on the housing side of the project, referring to both academic and policy literature in housing and pointing to the major gap that exists in relation to underemployment and housing outcomes such as housing security. The paper concludes with a brief discussion of our research strategy, including our research questions and data sources. The rationale for the research project (Chapter 1) builds on the familiar rationale for examining the connection between labour market conditions such as unemployment, or joblessness in general, and housing. Such labour market conditions can cause severe housing problems for affected individuals and households and can present substantial challenges to housing policy. It is widely accepted, in particular, that unemployment can negatively affect housing security, though in complex and indirect ways. We use the notion of secure housing to refer to housing that allows residents to plan ahead with minimal anxiety about the future and to choose whether and when to stay or leave. On the other hand, housing insecurity arises when circumstances are such that residents cannot plan ahead because their housing arrangements are threatened by financial factors, insecure tenancy arrangements or some other hazard. Housing insecurity also arises when individuals and families are excluded from conventional or culturally accepted forms of housing. This project is concerned with a labour market feature that closely resembles unemployment—what is commonly called underemployment. By underemployment we mean time-related underemployment, broadly understood as employment that is insufficient in terms of the number of hours of paid work. Underemployment is closely related to the concept of unemployment: thus both involve a notion of insufficient hours of paid work; both are linked in official labour force statistics as aspects of labour force underutilisation; both represent a measure of the labour force status of individuals; both involve a subjective preference as one element in the definition (a wish to find more hours of paid work in the case of the underemployed and a wish to find a job in the case of the unemployed); and both involve what could be seen as a transitional state on the way to and/or from a desired state of adequate employment. Underemployment has begun to attract attention from labour market researchers and policy-makers, partly in response to the compelling evidence that underemployment has become increasingly significant as a reserve of underutilised labour in Australian labour markets. Underemployment has been given a careful definition and is now frequently joined together with unemployment in official measures of labour underutilisation. Underemployment resembles unemployment and is an increasingly significant feature of Australian labour markets. We can hypothesise that, as in the case of unemployment, underemployment is likely to have a negative effect on housing outcomes, including housing security. Yet the connection between underemployment and housing insecurity has not been thoroughly examined by housing researchers and policy-makers. Our research project aims to fill this important knowledge and policy gap.